Contextualising Generic and Universal Generalisations: Quantifier Domain Restriction and the Generic Overgeneralisation Effect. (14th October 2019) - Lazaridou-Chatzigoga, Dimitra; Stockall, Linnaea; Katsos, Napoleon
Abstract: Generic generalisations (e.g. 'tigers have stripes', 'ducks lay eggs') refer to a characteristic property of a kind. Recently, the generics-as-default view has posited that we have a bias towards interpreting universally quantified statements as generic. Evidence offered for this view is the Generic Overgeneralisation (GOG) effect, which refers to the documented tendency of participants to misinterpret a quantificational statement like 'all ducks lay eggs' as if it were a generic and thus accept it as true, even though they know it is false. Across two experiments in English and Greek we systematically addressed the relevance of context and quantifier domain restriction for this kind of behaviour. Participants judged generic majority characteristic statements like 'tigers have stripes' or statements with universal quantifiers with different sensitivity to quantifier domain restriction preceded by one of three levels of context (neutral, contradictory and supportive). We found that context significantly affected the rates at which participants accepted universally quantified statements. Our results demonstrate that quantifier domain restriction is a viable alternative explanation for a significant proportion of the judgements of universally quantified statements that have been called GOG errors.